2023
DOI: 10.1080/15502783.2023.2214108
|View full text |Cite
|
Sign up to set email alerts
|

Repeated mouth rinsing of coffee improves the specific-endurance performance and jump performance of young male futsal players

Abstract: Background Mouth-rinsing with ergogenic solutions such as carbohydrate and caffeinated drinks has been considered among athletes as a practical nutritional strategy. Therefore, this study aimed to determine the effect of repeated coffee mouth-rinsing (CMR) doses on specific performances of futsal players. Method Twenty-four male futsal players randomly participated in this randomized, double-blind, and crossover design study. During the intervention, participants were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Previous studies have also shown the positive effects of caffeine on agility performance [ 37 , 38 , 39 ], vertical jump [ 11 , 22 , 40 , 41 , 42 , 43 ], or special volleyball skills [ 23 , 24 ]. Several meta-analyses have also confirmed that caffeine can improve vertical jump [ 26 , 44 , 45 , 46 ] or agility performance [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also shown the positive effects of caffeine on agility performance [ 37 , 38 , 39 ], vertical jump [ 11 , 22 , 40 , 41 , 42 , 43 ], or special volleyball skills [ 23 , 24 ]. Several meta-analyses have also confirmed that caffeine can improve vertical jump [ 26 , 44 , 45 , 46 ] or agility performance [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine is rapidly distributed in the body and affects the central nervous, respiratory, cardiovascular, and musculoskeletal systems [ 10 , 11 ]. Caffeine blood level increases 15 min after consumption, and the peak of its increase is after 60 min [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a relatively low absolute dose of caffeine (300 mg) given as gum, 10 min before exercise, has been reported to be effective for acute improvements in vertical jump height, lower body muscle strength, and total body strength in resistance-trained men [ 44 ]. Also, repeated CMR improved vertical jump performance in futsal players [ 15 ]. However, some studies showed inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…In PLA condition, participants consumed one capsule containing 5 grams of starch 45 minutes before the start of the tests ( Figure 2 ). All trials were completed at approximately the same time of day (Between 10–11 am) and all participants were fed the same breakfast containing 350–400 kcal (64% carbohydrates, 20% protein and 16% fat) 2 hours before the exercise test session [ 15 ]. Participants were instructed to maintain their normal diet throughout the testing period, to avoid food an hour before testing, and to avoid strenuous exercise 24 hours before each trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation